2022
DOI: 10.1061/(asce)co.1943-7862.0002243
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Mental Stress on Physical Stress for Construction Tasks

Abstract: Because of labor-intensive and physically demanding tasks, construction workers are known to be at a higher risk of developing physical fatigue. Recently, studies have shown that construction workers are often exposed to considerable mental stresses as well. While a number of studies have proposed methods and tools to measure and monitor physical and mental stress disjointedly, there is a need to explore their interaction. The literature indicates that no previous study has endeavored to evaluate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…14 Studies showed that construction workers are often exposed at the same time to physical and mental stress, being necessary to simultaneously monitor both the conditions to better evaluate the job strain. Umer et al 15 set the goal of monitoring carefully and simultaneously the physical and mental stress, using physiological measures and learning algorithms. To prove that in 2021, they carried out a survey that revealed that using only physiological measurements does not give a complete range of the psychological disorders of construction workers.…”
Section: Learning Outcomesmentioning
confidence: 99%
“…14 Studies showed that construction workers are often exposed at the same time to physical and mental stress, being necessary to simultaneously monitor both the conditions to better evaluate the job strain. Umer et al 15 set the goal of monitoring carefully and simultaneously the physical and mental stress, using physiological measures and learning algorithms. To prove that in 2021, they carried out a survey that revealed that using only physiological measurements does not give a complete range of the psychological disorders of construction workers.…”
Section: Learning Outcomesmentioning
confidence: 99%
“…To assess work-related stressors and organisation-related stressors, the scale developed by Ng, Skitmore and Leung (2005) was adopted. Similar studies in the recent past also adopted Ng, Skitmore and Leung (2005) scale to study occupational stress in other contexts (Zheng, et al, 2021;Zhang and Bowen, 2021;Umer, Yu and Afari, 2022). To assess the components of work-life balance, a 24-item scale developed by Fisher, Bulger and Smith (2009) was adopted for the present study.…”
Section: Measures Of Occupational Stress and Work-life Balancementioning
confidence: 99%
“…For instance, construction workers are 1.7 times more likely than workers in general industries to suffer from psychological health issues, including emotional and stress-related injuries [ 20 ]. Stress is mainly due to various aggravators such as the harsh outdoor environment, physically demanding tasks, time pressure, interpersonal conflicts and insufficient management support [ 21 ]. The COVID-19 pandemic may further deteriorate this situation by disrupting the construction activities, and bringing about other stressors such as pandemic fear and job insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic may further deteriorate this situation by disrupting the construction activities, and bringing about other stressors such as pandemic fear and job insecurity. Working under excessive stress could have adverse effects such as higher mistakes and accident risks, lowered productivity and mental health illnesses [ 21 ]. The construction industry is labor-intensive, and workers are directly responsible for the success of construction projects [ 22 ].…”
Section: Introductionmentioning
confidence: 99%